Piloting innovations for improved data collection and management to support livestock monitoring, reporting, and verification (MRV) of greenhouse gas emissions in Ethiopia - Eshete, Shimels; Tadesse, Million; Baker, Derek; Wilkes, Andreas; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
To complement an ongoing CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) project ‘Enhancing capacities for MRV of sustainable livestock action in East Africa (Kenya and Ethiopia),’ which is implemented by UNIQUE forestry and land use and CCAFS, the Australian Centre for International Agricultural Research (ACIAR) supported CCAFS to implement a Small Research Activity (SRA) entitled ‘Building capacities for an integrated livestock MRV system in Ethiopia’. The objective of the SRA was to support Ethiopian stakeholders to improve the methods and procedures used to produce and manage the livestock activity data required for measurement, reporting and verification (MRV) of greenhouse gas (GHG) emissions in Ethiopia. This report summarizes the rationale for and overall design of the pilot activities, pilot results, stakeholders’ evaluations of the tools tested, and recommendations for adoption of positively evaluated tools. Section 1 explains the rationale for piloting tools to collect livestock activity data in the Ethiopian context. Ethiopia has identified livestock as a key sub-sector for GHG mitigation. An advanced livestock GHG inventory has been compiled using the Tier 2 method. However, some gaps remain in terms of data availability and data quality. The pilot activities were designed to fill those gaps, and thus enable Ethiopia to better quantify livestock GHG emissions and emission reductions in line with its national commitments on climate change. Section 2 describes the design of the pilot activities. The Tier 2 GHG inventory uses annual sample surveys from Central Statistics Agency (CSA) for data on many variables. Some tools were tested to see if they would lead to improvements in CSA data collection methods for the purpose of the GHG inventory. Some data gaps in the GHG inventory require specialist knowledge and tools and they were tested for data collection by staff of the Ministry of Agriculture or other stakeholders with technical backgrounds. In addition to data collection, data management and communication are key to ensuring that the data is available to those who can make use of it. A further pilot involved the Ethiopian Institute for Agricultural Research (EIAR) in analysis and communication of data. Section 3 summarizes the results of the pilot activities on diet composition, manure management, milk yield including stakeholders’ evaluation of different data collection tools and data management activities. In addition to the accuracy of different data collection tools, stakeholders evaluated the tools tested in relation to other criteria such as cost-effectiveness and ease of adoption within existing data management systems. Section 4 highlights key recommendations for the adoption of the tools and data management activities evaluated by stakeholders. Some tools can be readily adopted by existing actors in existing data management systems. Other tools were positively evaluated but further discussion is needed to clarify the roles and responsibilities for their use. The tools tested can also be used by other stakeholders, such as the Oromia Forested Landscape Programme. This section ends with some reflections on the piloting process from the project team, which may provide some guidance for future piloting of MRV innovations elsewhere in East Africa.